The use of social media by professors in teaching and learning practices of undergraduate business administration classroom - Volles, Barbara Kobuszewski, 1989- (2016)
Dissertação - Universidade Regional de Blumenau, Centro de Ciências Sociais Aplicadas, Programa de Pós-Graduação em Administração, Blumenau, 2016.